beta-Galactosidase containing a human immunodeficiency virus protease cleavage site is cleaved and inactivated by human immunodeficiency virus protease. - Baum, E Z (1990)
A "cleavage cassette" specifying a decapeptide human immunodeficiency virus (HIV) protease cleavage site was introduced into six different locations of beta-galactosidase (beta-D-galactoside galactohydrolase, EC 3.2.1.23) in Escherichia coli. Four of these constructs retained beta-galactosidase activity despite the insertion of the cleavage cassette. Of these four constructs, one was cleaved by HIV protease, resulting in the inactivation of beta-galactosidase both in vivo and in vitro. This cleavage was inhibited by pepstatin A, a known inhibitor of HIV protease. Thus, beta-galactosidase has been converted into an easily assayed substrate for HIV protease. An analogous construct of beta-galactosidase containing a polio protease cleavage site was cleaved likewise by polio protease, suggesting that this system may be generic for monitoring cleavage by a variety of proteases.